Reversal of Obesity: The Quest for the Optimum Dietary Regimen - Nicoll, Rachel (International Journal of Nutrition, 2017)
A new approach to weight loss and weight loss maintenance is urgently needed, with the global epidemic of obesity leading to ever higher levels of chronic disease. This new approach should be cheap and simple, it should maintain essential nutrients and not deplete lean mass, should have minimal adverse effects and be carried out safely at home without support from the healthcare profession. This review looked at the forms of caloric restriction (CR) investigated in randomised controlled trials (RCTs) and found that supervised continuous and intermittent CR was more effective than other forms of weight loss over periods from 12 weeks to 2 years and could improve cardiovascular and diabetes risk factors. CR was equally as effective as bariatric surgery, suggesting that it is the post-surgery caloric restriction that has the impact on weight, rather than the surgery itself. Intermittent CR, including alternate day fasting (ADF), was as effective as continuous CR but may show improved compliance and higher lean mass. Unsupervised weight loss maintenance presents a greater problem, since in most weight loss regimens all the weight lost is ultimately regained. Although both continuous and intermittent CR can be effective, it has been found that ADF and a higher protein intake is more likely to maintain the weight loss. These results hold for all age groups and ethnicities and both genders. These findings suggest that intermittent CR, and particularly ADF, may be a viable form of weight loss and maintenance which fulfils all the criteria above. It is therefore recommended that larger RCTs investigate intermittent CR and ADF as a viable and cost effective form of weight loss and weight loss maintenance.
Keywords: Obesity; type 2 diabetes; caloric restriction; fasting